2018
DOI: 10.4269/ajtmh.17-0553
|View full text |Cite
|
Sign up to set email alerts
|

Survey to Identify Substandard and Falsified Tablets in Several Asian Countries with Pharmacopeial Quality Control Tests and Principal Component Analysis of Handheld Raman Spectroscopy

Abstract: The World Health Organization has warned that substandard and falsified medical products (SFs) can harm patients and fail to treat the diseases for which they were intended, and they affect every region of the world, leading to loss of confidence in medicines, health-care providers, and health systems. Therefore, development of analytical procedures to detect SFs is extremely important. In this study, we investigated the quality of pharmaceutical tablets containing the antihypertensive candesartan cilexetil, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Further, there were sporadic reports concerning Myanmar in 2001 and 2008 [7,8]. Therefore, we started a survey in Myanmar in 2014 [9,10], and followed that with the present in 2015. Because the number of patients with long-term diseases in developing countries is increasing [11], not only on anti-microbials, but also on medicines against chronic or life-style related diseases are important.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there were sporadic reports concerning Myanmar in 2001 and 2008 [7,8]. Therefore, we started a survey in Myanmar in 2014 [9,10], and followed that with the present in 2015. Because the number of patients with long-term diseases in developing countries is increasing [11], not only on anti-microbials, but also on medicines against chronic or life-style related diseases are important.…”
Section: Introductionmentioning
confidence: 99%
“…Moisture absorption because of poor storage conditions, such as high temperature and high humidity, might be one of the causes of quality deterioration. It has been reported that tablets contain a large amount of high specific gravity ingredients, even in falsified medicines that may be manufactured in a sloppy manner ( Kakio et al, 2018 ). The poor dissolution in RXM tablets might be because of the manufacturing process.…”
Section: Discussionmentioning
confidence: 99%
“…It is pointed out by heads of state and the WHO that universal health coverage (UHC, Good Health and Well-being) as described in Sustainable Development Goal 3.8 (SDGs) cannot be achieved without ensuring the quality of medicines. In many countries, especially low- and middle-income countries (LMICs), medicine regulation authorities, manufacturers, and researchers are struggling to prevent the distribution of SFMs ( Lon et al, 2006 , Amin and Kokwaro, 2007 , Gaudiano et al, 2007 , Khan et al, 2010 , Khan et al, 2011a , Khan et al, 2011b , Binagwaho et al, 2013 , Yoshida et al, 2014 , Otte et al, 2015 , Petersen et al, 2017 , Yong et al, 2015 , Kakio et al, 2017 , Khuluza et al, 2017 , Kakio et al, 2018 , Pisani et al, 2019 , Tabernero et al, 2019 , Schäfermann et al, 2020 ). However, the prevalence of SFMs is currently increasing globally, especially in LMICs, where the proportion of SFMs has reached 10.5% of the pharmaceutical market ( WHO, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cash-Goldwater et al 11 Infection risk factors Brucellosis confirmed by blood culture, or 4-fold rise in microagglutination was confirmed or probable in 9% of febrile patients, mostly who attend animals but were not suspected by medical providers. Kakio et al 12 Medication quality Studies of dissolution and use of handheld Raman spectrophotometer device were useful in detecting substandard or falsified medications using the antihypertensive candesartan as a test product. Fauver et al 13 Xenosurveillance PCR detected Trypanosoma brucei gambiense, Bacillus anthracis, Middle East respiratory syndrome-related Coronavirus, and Zika virus in the blood of Anopheles gambiae mosquitoes fed on blood containing these pathogens.…”
Section: Natural Selectionsmentioning
confidence: 99%